2021
DOI: 10.1039/d0ra08817j
|View full text |Cite
|
Sign up to set email alerts
|

Anti-rheumatic effect of quercetin and recent developments in nano formulation

Abstract: Quercetin is a potential anti-rheumatoid drug. Nano formulation strategies could improve its solubility and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 101 publications
(121 reference statements)
0
11
0
1
Order By: Relevance
“…Overall, there are several strategies that can be adopted to increase the solubility and subsequent bioavailability of flavonoids with therapeutic potential. Although much progress has been recently made, novel drug delivery systems suitable for an optimized topical application should continue to be explored [ 112 , 154 , 155 , 156 , 157 ]. A summary of the therapeutic application of flavonoids and the different nanocarriers used to enhance their delivery to the skin is described in Table 3 .…”
Section: Cutaneous Delivery Systems Of Flavonoids For Treatment Of Skin Pathologiesmentioning
confidence: 99%
“…Overall, there are several strategies that can be adopted to increase the solubility and subsequent bioavailability of flavonoids with therapeutic potential. Although much progress has been recently made, novel drug delivery systems suitable for an optimized topical application should continue to be explored [ 112 , 154 , 155 , 156 , 157 ]. A summary of the therapeutic application of flavonoids and the different nanocarriers used to enhance their delivery to the skin is described in Table 3 .…”
Section: Cutaneous Delivery Systems Of Flavonoids For Treatment Of Skin Pathologiesmentioning
confidence: 99%
“…In certain diseases like rheumatoid arthritis, ulcer, etc., inflammation worsens the disease profile due to the release of inflammatory mediators. Research confirmed quercetin’s anti-inflammatory effect was due to inhibition of proinflammatory cytokines, ATP and nuclear factor kappa B (IkBa) binding sites [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 35 Recently, the potential effects of important natural plant-based compounds and their derivatives such as resveratrol, curcumin, matrine, quercetin, and sylimarin, have been extensively investigated on a variety of disorders including autoimmunity. 16 , 36 43 The majority of natural/herbal medications can control different diseases by inhibiting pro-inflammatory mediators and increasing the frequency and activity of Tregs. 36 , 44 46 Therefore, medicinal plants are important sources for development of new immunomodulatory and anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%